NATO Arctic policy in statu nascendi - Podvorna, Olena; Zhovtenko, Taras (ROU, 2019)
Having played a substantial role in the bipolar period, the Arctic has found itself at the "backyard" of international politics after the Cold War. During the last decade of the XXth century, the Arctic was the priority issue only for the littoral states. The Russian expedition to the North Pole in the so-called "last scramble" for energy resources drew regional interest of a wide range of international actors, including NATO. The Alliance faced a serious task of elaborating its policy in the Arctic to meet its member-states' and associated partners' modern-day reality expectations. NATO started close cooperation with Norway trying to shape a policy that could bring an added value to the region in terms of positive security thinking, largely dominating European agenda after the Cold War. However, a rapid change of the security situation since the beginning of the Russian-Ukrainian conflict has shifted the Alliance's agenda towards the continent and its relations with Moscow raising concerns about the revival of the traditional bipolar thinking about the security and prospective remilitarization of the Arctic. It is vital for the Alliance to shape its policy, both strategically and tactically, to face those security challenges and guarantee peace and stability in the Arctic.